Correlation of Normal Diastolic Cardiac Function with VO(2 max) in Metabolic Syndrome - Chockalingam, Anand (2009)
BACKGROUND: Morbid obesity and diabetes cause diastolic dysfunction that can be detected by Doppler echocardiography. Metabolic syndrome subjects could demonstrate early diastolic dysfunction which may influence effort tolerance (VO(2 max)). METHODS AND RESULTS: 32 subjects (17 males) who fulfilled 2 or more of the 5 metabolic syndrome criteria were studied. Average age was 37 ± 2 years. All were overweight-obese (mean BMI of 34.4 ± 0.7 kg/m(2)), 15 had BP > 130/85mmHg, 19 had elevated triglycerides (>150mg/dl) and 17 had low HDL cholesterol (males <40 mg/dl, females <50 mg/dl). Maximal exercise was performed using Bruce treadmill protocol with standard stress echocardiography and tissue Doppler. Maximal oxygen consumption (VO(2 max)) was measured using indirect calorimetry. LV filling pressure was indirectly derived from dividing pulse Doppler early mitral inflow velocity (E) by tissue Doppler early diastolic mitral annular motion (E′) or E/E′. The group's average treadmill time was 8.06 ± 0.28 minutes, VO(2 max) was 28.6±1.1 ml/kg/min and 8.2 ±0.3 METs. None had evidence for myocardial ischemia, systolic or diastolic dysfunction with exercise. Mean resting E/E′ and post exercise E/E′ were 7.01 ± 0.04 and 7.41 ± 0.41 respectively. There was no significant correlation between resting E/E′ and VO(2 max) (r= -0.266, p=0.14). The post exercise E/E′ significantly correlated with VO(2 max) (r= -0.483, p=0.005) and METs (r= -0.487, p=0.005). CONCLUSIONS: Diastolic function is preserved in early metabolic syndrome. Even in the normal diastolic function range, exercise E/E′ is inversely related to VO(2 max). Further longitudinal studies are needed to determine if they develop diastolic dysfunction and related heart failure.